Natural products, A.R.T. & infertility - Abdul Rahman, Suzanah (2016)
The consumption of natural products and its supplementation in traditional and complimentary medicine has always been the mainstay of treatment of diseases and ailments especially in developing countries. With the advancement in medical therapy and technology, the concurrent use of natural products to remedy numerous illness does not abate and the trend has increased over the years. Natural products of plant origin initiated herbalism, an ancient tradition of application of herbs for their healing properties. Different parts of indigenous plants have been selected and harnessed for their varying therapeutic effects and methods of administration ranged from herb-infused tea, honey, oil, creams and poultices. The effects of natural products on the growth of cells and their restorative properties have been documented in numerous studies and their bioactivity is driven by the various chemical compositions and the active ingredients in each type of plant. The application of natural products to treat infertility and problems associated with sexual dysfunctions has long been practised in traditional remedies in pursuit of preserving lineage. Assisted Reproductive Technology (ART) is a set of techniques comprising of methods such as artificial insemination and in vitro fertilization (IVF) to achieve successful pregnancy. Work using prominent natural products in ART and their effects on the reproductive cells and embryo have shown potential in the merge of old practices to new techniques to achieve fertilization of quality and in ameliorating adverse environmental effects impacting fertility.